Ets-1 interacts through a similar binding interface with Ku70 and Poly (ADP-Ribose) Polymerase-1. Issue 10 (3rd October 2018) - Choul-li, Souhaila; Legrand, Arnaud J.; Vicogne, Dorothée; Villeret, Vincent; Aumercier, Marc
ABSTRACT: The Ets-1 transcription factor plays an important role in various physiological and pathological processes. These diverse roles of Ets-1 are likely to depend on its interaction proteins. We have previously showed that Ets-1 interacted with DNA-dependent protein kinase (DNA-PK) complex including its regulatory subunits, Ku70 and Ku86 and with poly (ADP-ribose) polymerase-1 (PARP-1). In this study, the binding domains for the interaction between Ets-1 and these proteins were reported. We demonstrated that the interaction of Ets-1 with DNA-PK was mediated through the Ku70 subunit and was mapped to the C-terminal region of Ets-1 and the C-terminal part of Ku70 including SAP domain. The interactive domains between Ets-1 and PARP-1 have been mapped to the C-terminal region of Ets-1 and the BRCA1 carboxy-terminal (BRCT) domain of PARP-1. The results presented in this study may advance our understanding of the functional link between Ets-1 and its interaction partners, DNA-PK and PARP-1. Graphical Abstract: Mapping of Ets-1/Ku70 and Ets-1/PARP-1 interaction domains.